2007
DOI: 10.1074/jbc.m611297200
|View full text |Cite
|
Sign up to set email alerts
|

The Conserved CPH Domains of Cul7 and PARC Are Protein-Protein Interaction Modules That Bind the Tetramerization Domain of p53

Abstract: Cul7 is a member of the Cullin Ring Ligase (CRL) family and is required for normal mouse development and cellular proliferation. Recently, a region of Cul7 that is highly conserved in the p53-associated, Parkin-like cytoplasmic protein PARC, was shown to bind p53 directly. Here we identify the CPH domains (conserved domain within Cul7, PARC, and HERC2 proteins) of both Cul7 and PARC as p53 interaction domains using size exclusion chromatography and NMR spectroscopy. We present the first structure of the evolut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
49
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(52 citation statements)
references
References 45 publications
3
49
0
Order By: Relevance
“…While this manuscript was in preparation, a direct interaction between ectopic p53 and Cul7 was reported by others (24)(25)(26), which confirms our findings. Unlike the interaction between PARC and p53 (19), the Cul7/ p53 interaction does not seem to influence p53 localization (24).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…While this manuscript was in preparation, a direct interaction between ectopic p53 and Cul7 was reported by others (24)(25)(26), which confirms our findings. Unlike the interaction between PARC and p53 (19), the Cul7/ p53 interaction does not seem to influence p53 localization (24).…”
Section: Discussionsupporting
confidence: 92%
“…Because several E3 ligases have been shown to mono-and di-ubiquitinate p53 (11,(13)(14)(15), it is possible that immunoprecipitates of Cul7/p53 contain other E3-ligases responsible for the in vitro ubiquitination of p53 observed by Andrews et al (24). The association of Cul7 with p53 was shown to occur with oligomeric forms of p53 (26) and tetrameric p53 is less efficiently imported into the nucleus than its monomeric form (31). Ectopic Cul7 interfered with p53 activation in response to DNA damage when cytoplasmic and nuclear p53 levels are increased.…”
Section: Discussionmentioning
confidence: 97%
“…The HERC2-binding domain of p53 was located in its carboxyl terminus, similar to other p53-binding proteins with CPH domains, such as PARC and CUL7 (6 -8). Structural studies of the CPH domain of PARC and CUL7 indicated that this domain interacts with the tetramerization domain of p53 (residues 310 -360) (49). In agreement with these data, deletion of the last 43 amino acid residues of p53 (residues 350 -393) impaired the interaction with HERC2 (Fig.…”
Section: Discussionsupporting
confidence: 79%
“…This diverse fold bears many similarities to KOW [24], CPH [25] and SH3 domains [26], of which some are shown in Fig. 4 for comparison.…”
Section: Resultsmentioning
confidence: 99%